PERAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH: STUDI LITERATUR - Muhammad Ilham Rezki Wijaya Ilham; Dhea Pramestie Aryani Dhea; Rahmat Al Ghaffari Prahasa Rahmat; Mudriko Ahyulindo Riko; Rika Henda Safitri Rika (Jurnal Riset Akuntansi, 2026)
The quality of local government financial reporting serves as a crucial benchmark for measuring transparency and public accountability. Internal oversight efforts in the financial reporting process can reveal various outcomes in administration and audit assessments, including the weaknesses of such oversight. This study aims to analyze the implementation of the Internal Control System (ICS) that can influence the quality of financial reports across various regions in Indonesia using a Literature Review approach based on 20 previous articles discussing similar conditions. Article screening was conducted in accordance with the PRISMA protocol guidelines to ensure the collection of high-quality data. The following findings indicate that the accuracy and reliability of financial data are significantly impacted by the implementation of ICS guided by the COSO/SPIP framework. Furthermore, to maintain the effectiveness of the ICS, enhanced leadership commitment and competent human resources at the government agency level are essential, including regular monitoring to minimize fraudulent activities in accounting management.